Lower repetition induces similar postactivation performance enhancement to repetition maximum after a single set of heavy-resistance exercise - Chen, C.-F.; Chuang, C.-Y.; Wang, C.-C.; Liu, S.-A.; Chang, H.-W.; Chan, K.-H. (The Journal of Strength and Conditioning Research, 2024)
The study was divided into 2 parts to investigate the acute postactivation performance enhancement (PAPE) responses to lower repetitions at the same load of 87% 1 repetition maximum (1RM) in the upper and lower body. In part 1, 14 athletes performed plyometric push-up (PPU) after the conditioning activity (CA) of bench press (BP). In part 2, 13 athletes performed a countermovement jump (CMJ) after the CA of parallel squat (PS). Subjects completed 3, 4, or 5 repetitions (trials CA-3, CA-4, or CA-5) of BP or PS in randomized and counterbalanced order. The velocity of each movement of the trial was recorded. The PPU or CMJ was tested every 2 minutes after the trial up to 12 minutes to assess the Post-Max and optimal individual PAPE time. The mean velocity of the last movement of BP in CA-5 was significantly lower than that in CA-3 (0.23 ± 0.06 vs. 0.28 ± 0.06 m·second-1, p < 0.05), and the velocity of PS in CA-4 or CA-5 was significantly lower than that in CA-3 (0.53 ± 0.07 and 0.50 ± 0.05 vs. 0.57 ± 0.07 m·second-1, p < 0.05). The peak force of PPU and jump height of CMJ at Post-Max in the 3 trials were significantly greater than those at Pre (p < 0.05). There were no significant differences among trials in the optimal individual PAPE times in either part of the study. A single set of 87% 1RM resistance exercises with 3 or 4 repetitions in both the upper body and the lower body induces similar PAPE to repetition maximum.